A Pervasive Application Rights Management Architecture (PARMA) based on ODRL - DUSPARIC, IVANA (My University, 2004)
Software license management is currently expanding from its traditional desktop environment into the mobile application space, but software vendors are still applying old licensing models to a platform where application rights will be specified, managed and distributed in new and different ways. This paper presents an open-source pervasive application rights management architecture (PARMA) for fixed network and mobile applications that supports the specification of application rights in a rights expression language (REL) based on ODRL. Our rights specification model uses aspectoriented programming to generate modularized rights enforcement behaviour, which reduces development time for rights models such as feature-based usage rights and nagware. PARMA manages vendor and customer application rights over multiple platforms using a web services architecture and a container model on the client-side. The container model also supports the integration of services such as payment and encourages the super distribution of the rights object with associated default (evaluation) rights.
Proceedings of the First International Open Digital Rights Language (ODRL) Workshop
First International Open Digital Rights Language (ODRL) Workshop
PUBLISHED
Keywords: Application Rights Management, Pervasive Computing, ODRL, Aspect-Oriented